Analisis Produktivitas Tenaga Kerja Pada Proyek Pembangunan Ruang Laboratorium Komputer SDN 7 Lembo Kabupaten Konawe Utara - Sufrianto Sufrianto; Vickky Anggara Ilham; Wa Ode Mini (Universitas Sulawesi Tenggara, 2026)
The difference between productivity in the field and reference productivity can cause discrepancies between project planning and its implementation. This may result in resource wastage, cost inefficiency, and disruption of the project schedule. Therefore, an in-depth study is needed to determine the actual level of labor productivity occurring in the field. This study was conducted to analyze labor productivity in red brick wall masonry and wall plastering work on the Computer Laboratory Room Construction Project at SDN 7 Lembo. The purpose of this study is to calculate the actual labor productivity value and compare it with the reference productivity based on applicable regulations. Through this research, it is expected to provide an overview of the level of labor efficiency. This research was conducted through direct observation in the field. Observations were carried out on red brick masonry and wall plastering work. The aspects observed included the work volume, number of workers, and the duration of work per day. The results of this study show that the average labor productivity in the field is 5.53 m²/OH for brick masonry work and 22.79 m²/OH for plastering work. The standard labor productivity value according to the reference (Permen PUPR 2025) for brick masonry work is 4.76 m²/OH, and for wall plastering work it is also 4.76 m²/OH. The comparison of productivity values is 1.16 m²/OH for brick masonry work and 4.78 m²/OH for plastering work. Based on these results, the field productivity is higher than the productivity according to the reference standard.